1993
DOI: 10.1177/036354659302100506
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of meniscal tears in anterior cruciate ligament insufficiency

Abstract: We reviewed the meniscal status of 176 consecutive patients undergoing anterior cruciate ligament reconstruction acutely (less than 6 weeks from injury), subchronically (6 weeks to 12 months from injury), and chronically (more than 12 months from injury). The commonest tear was the single longitudinal vertical split of the medial meniscus. There was an increasing incidence of meniscal tears as the injury became more chronic, with a significant (P < 0.001) increase in medial meniscal tears; the incidence of lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
155
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(166 citation statements)
references
References 32 publications
10
155
0
1
Order By: Relevance
“…With each episode of giving way, meniscal tears can become more complex and less amenable to repair [8]. Studies in adult patients [7,8,24,39] and in pediatric patients [12,28,32] have shown an increased incidence of medial meniscal tears with delayed ACL reconstruction. Although the treatment of ACL tears in skeletally immature patients remains controversial [33], the risk of physeal injury and resulting growth disturbance from ACL repair to a patient with open physes is now thought to be small [15,22], and many centers (including our institution) opt for prompt reconstruction before skeletal maturity [9,16,20,25,31,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…With each episode of giving way, meniscal tears can become more complex and less amenable to repair [8]. Studies in adult patients [7,8,24,39] and in pediatric patients [12,28,32] have shown an increased incidence of medial meniscal tears with delayed ACL reconstruction. Although the treatment of ACL tears in skeletally immature patients remains controversial [33], the risk of physeal injury and resulting growth disturbance from ACL repair to a patient with open physes is now thought to be small [15,22], and many centers (including our institution) opt for prompt reconstruction before skeletal maturity [9,16,20,25,31,34,40].…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of these studies, it seems that the outcome of a repair is better with concomitant reconstruction than in knees that remain unstable or even better than knees without ACL injury. [10][11][12][13][14][15] It must be assumed that in the subgroup of patients with concomitant ACL reconstruction, the main reason for the procedure is instability, and that conclusively not only symptomatic but also clinically silent lesions of the meniscus are identified and repaired. However, in patients with stable knees, the cause for the meniscus repair usually is meniscus symptoms, such as locking or effusion.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of ACL function increases tibial translation, allowing the meniscus to "engage" the femoral condyle and act as a wedge against the tibia [22,23], while others have suggested that mechanical trauma causes the MMTs in this setting [12,18,20]. Several studies have explored the relationship between ACL injury and meniscal tear [24][25][26][27][28][29][30]. Some showed preponderance of the LMTs in the acute setting and in osteoarthritis [24,25], others suggested the MMTs especially in acute reconstructions [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the relationship between ACL injury and meniscal tear [24][25][26][27][28][29][30]. Some showed preponderance of the LMTs in the acute setting and in osteoarthritis [24,25], others suggested the MMTs especially in acute reconstructions [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%